Climate change effects on the potential distribution of the endemic Commiphora species (Burseraceae) on the island of Socotra - La Montagna, Dario; Attorre, Fabio; Hamdiah, Salem; Maděra, Petr; Malatesta, Luca; Vahalík, Petr; Van Damme, Kay; De Sanctis, Michele (Frontiers in Forests and Global Change, 2023)
The Socotra Archipelago (Yemen) is an interesting biodiversity hotspot, with a significant proportion of endemic species that have evolved to survive in an arid subtropical environment, inscribed as a Natural Heritage Site by UNESCO. The terrestrial ecosystems of Socotra face several threats, including climate change, overgrazing and soil degradation. Within these, are present four endemic species of the genus Commiphora (Burseraceae), which little is known about the distribution and ecology, and they can be used as indicator species. This study focuses on the distribution and niche characterisation of the four endemic Commiphora species and how climate change will likely affect them, to provide insights into their habitats and an essential basis for future local management plans and ecological restoration. We compared the current distribution and forecast potential distribution under a CMIP6 (Coupled Model Intercomparison Project) climate scenario, allowing us to define target conservation areas and assess potential local extinction risks. To achieve this, we collected distribution data in the field throughout Socotra Island, covering the four species current distribution ranges. To assess the potential distribution of these species, we applied three models (GAM, MaxEnt, RandomForest) using bioclimatic, topographic and soil variables. Forecasts under a climate change scenario were made using bioclimatic variables from the CMCC-CESM2 climate model for two different socioeconomic pathways. The distribution of three endemic Commiphora of Socotra is mainly determined by clay content in the soil and winter precipitation, while the fourth, C. socotrana, is affected by seasonal precipitation and temperature. Under different potential future climate scenarios, the C. ornifolia distribution is predicted to remain stable or increase, while C. parvifolia shows an increase and C. planifrons is predicted to undergo a reduction of suitable areas and an upward shift in the mountains. The results highlight that it is essential to conserve the unique terrestrial ecosystems in Socotra and preserve the ethnobotanical values of the endemic trees with a wide range of ecosystem services. Updates on the predicted extinction risk assessment are fundamental to understand conservation priorities and strategize future actions to ensure the persistence of Socotra myrrh trees and other endangered endemic tree taxa.